2022
DOI: 10.1038/s41522-022-00335-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinically relevant pathogens on surfaces display differences in survival and transcriptomic response in relation to probiotic and traditional cleaning strategies

Abstract: Indoor surfaces are paradoxically presumed to be both colonized by pathogens, necessitating disinfection, and “microbial wastelands.” In these resource-poor, dry environments, competition and decay are thought to be important drivers of microbial community composition. However, the relative contributions of these two processes have not been specifically evaluated. To bridge this knowledge gap, we used microcosms to evaluate whether interspecies interactions occur on surfaces. We combined transcriptomics and tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…2 ; [ 94 ]), although the effectiveness of these compounds has not specifically been demonstrated in the built environment. Several studies have demonstrated that Bacillus intervention enhances the pathogen exclusion properties of the extant surface microbiome [ 95 , 96 ]. However, the lack of a defined mechanism of action behind such biocontrol suggests an urgent need to perform new studies aimed at elucidating these modalities.…”
Section: Techniques For Investigating the Microbiome Of The Built Env...mentioning
confidence: 99%
See 3 more Smart Citations
“…2 ; [ 94 ]), although the effectiveness of these compounds has not specifically been demonstrated in the built environment. Several studies have demonstrated that Bacillus intervention enhances the pathogen exclusion properties of the extant surface microbiome [ 95 , 96 ]. However, the lack of a defined mechanism of action behind such biocontrol suggests an urgent need to perform new studies aimed at elucidating these modalities.…”
Section: Techniques For Investigating the Microbiome Of The Built Env...mentioning
confidence: 99%
“…To test the activity of these spore sprays, a commercially available cleaner containing either Bacillus spp. spores or a spore-free version of the cleaner was applied to steel coupons; then, the coupons were inoculated with either Acinetobacter baumannii or K. pneumoniae [ 95 ]. The coupons were sampled at 3, 24, and 72 hours for colony-forming unit (CFU) enumeration to determine whether the presence of the cleaner, with or without Bacillus spores, decreased the survival rate of the pathogens compared to cleaner-free controls [ 95 ].…”
Section: Techniques For Investigating the Microbiome Of The Built Env...mentioning
confidence: 99%
See 2 more Smart Citations
“…A high adaptive capacity against physical–chemical factors as well as biofilm‐forming capacity could partly explain the persistence phenomenon (EFSA BIOHAZ Panel, 2018). Recent advances in next generation sequencing technologies have promoted a more detailed characterisation of persistent isolates through whole genome sequencing (WGS) and transcriptomics, and offer opportunities for the study of persistence episodes at processing plant level through the characterisation of the FFPE microbiome through metagenomics, which will provide information on the role of complex microbial communities and the cellular processes and microbial interactions driving microbial persistence in the FFPE (Fenner et al., 2021; Hu et al., 2022).…”
Section: Introductionmentioning
confidence: 99%